2005
DOI: 10.1093/aje/kwi097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Paternal Age on the Risk of Spontaneous Abortion

Abstract: The frequency of chromosomal anomalies in spermatozoa appears to increase with male age. Because these anomalies play a role in the etiology of spontaneous abortion, an influence of paternal age on risk of spontaneous abortion is plausible but not established. The aim was to characterize this influence in a prospective study among 5,121 California women, who as members of a prepaid health plan were interviewed in 1990 or 1991 when they were less than 13 weeks' pregnant and who were followed until the end of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 40 publications
4
133
2
4
Order By: Relevance
“…Only recently have studies begun to show possible connections between increased paternal age and both sporadic and recurrent pregnancy loss (Slama et al 2005;de La Rochebrochard et al 2006;Kleinhaus et al 2006;Puscheck and Jeyendran 2007). Data addressing paternal age and fetal aneuploidy, however, is extremely varied and conflicting.…”
Section: Fetal Aneuploidy In Sporadic and Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Only recently have studies begun to show possible connections between increased paternal age and both sporadic and recurrent pregnancy loss (Slama et al 2005;de La Rochebrochard et al 2006;Kleinhaus et al 2006;Puscheck and Jeyendran 2007). Data addressing paternal age and fetal aneuploidy, however, is extremely varied and conflicting.…”
Section: Fetal Aneuploidy In Sporadic and Recurrent Pregnancy Lossmentioning
confidence: 99%
“…47 Spontaneous abortions A case-control study of 13 865 women found that increasing paternal age is significantly associated with spontaneous abortion, independent of maternal age and multiple other factors. 54 Slama et al 55 observed that the risk of spontaneous abortion was almost twice higher among men aged .45 years than among those aged ,25 years. Paternal age of .40 years becomes relevant concerning miscarriages when the woman was .30 years old.…”
Section: Telomeres and Paternal Agementioning
confidence: 99%
“…Boxplots along the top and right side indicate data distribution according to each axis (with permission from Slama et al, 2005). risk of spontaneous miscarriage was attributed to maternal and paternal age to the same extent (Selvin and Garfinkel, 1976) with maternal and paternal effects being linear, although reproductive age patterns are usually represented as J-or U-shaped curves (Nybo Andersen et al, 2000;de la Rochebrochard and Thonneau, 2002).…”
Section: Paternal Effectsmentioning
confidence: 99%
“…Unexpectedly this difference was only seen among couples in which the woman's age was ,30 years, which could be explained by the fact that maternal risk factors for spontaneous miscarriage might be better controlled by the adjustment for maternal age in younger than older women, in whom other factors, not adjustable by the maternal age, may mask the paternal age effect (Slama et al, 2005). However, retrospective evaluations of spontaneous miscarriages are limited due to an important recall bias (Wilcox and Horney, 1984).…”
Section: Paternal Effectsmentioning
confidence: 99%
See 1 more Smart Citation